Healthy Education in The Middle of Pandemi Covid-19 Through The Use of Social Media - Fitri Fatonah; Sugiyanto Sugiyanto (Universitas Sebelas Maret, 2020)
Strategic and rapid efforts are needed to overcome the spread of Covid-19, one of them is by counseling through social media in order that scientific information is provided. The existence of so called Social Abdication Program of UNS in the form of Field Work Lecture addresses this issue, takes a theme